Sustainable Development Goals (SDGs): what can universities do on campus? / Dr. Muhammad Zarunnaim Wahab and Dr. Mohamad Hanif Abu Hassan - Wahab, Muhammad Zarunnaim; Abu Hassan, Mohamad Hanif (Universiti Teknologi MARA, Kedah, 2023)
Sustainable Development Goals (SDGs) is a concept that has sparked widespread debate and discussion around the world in recent times. The concept is a part of the United Nations’ sustainable development agenda, with the aim of ending poverty, protecting the planet and ensuring prosperity by 2030 through the establishment of 17 goals and 169 targets (UNDP, 2020; Vorisek & Yu, 2020). Generally, SDGs can be implemented in various settings, encompassing both small-scale activities and large-scale endeavours. The size of the projects or activities is not a determining factor; rather, the primary focus lies on the positive impacts generated by these initiatives. The key objective is to create meaningful and sustainable outcomes that align with the overarching goals of the SDGs.